Land Suitability Evaluation for Cardamom (Elettaria cardamomum) Cultivation in Sumber Rejo Village, Purwosari Subdistrict, Pasuruan Regency - Agus Zainur Roziqin; Purwadi Purwadi; Purnomo Edi Sasongko (The University of Lampung, 2026)
Market demand for cardamom (Elettaria cardamomum) continues to rise, yet its cultivation remains limited to specific regions with suitable environmental conditions. Therefore, land suitability evaluation is essential as a basis for planning the development of this commodity. This study aims to assess land suitability for cardamom cultivation in Sumber Rejo Village, Purwosari Subdistrict, Pasuruan Regency. The evaluation was based on physical and chemical soil properties, including pH, organic carbon (C-organic), cation exchange capacity (CEC), base saturation, as well as soil texture and slope. Samples were collected from two types of land use: dry land (tegalan) and coffee plantations, with a total of six sampling points. The results showed that soil pH ranged from 5.70 to 5.92 (S1), C-organic ranged from 1.61% to 2.79% (S1), CEC from 23.93 to 33.07 cmol/kg (S1), and base saturation was in average < 35% (S2). Overall, the study area falls into the moderately suitable (S2) category for cardamom cultivation with potential improvement to S1 through manure and compost application. This evaluation, however, was based on only four parameters so that future research should continue with other parameters to have a more comprehensive results on land suitability for cardamom cultivation in Sumber Rejo village.